Reddit sentiment analysis and topic modelling on POFMA - Ghazali, Aqil Akram (Nanyang Technological University, 2024)
The proliferation of misinformation in the digital age presents a pressing challenge globally, and Singapore has responded with the Protection from Online Falsehoods and Manipulation Act (POFMA). While POFMA aims to combat misinformation, concerns about its impact on freedom of speech persist. This study investigates public sentiment towards POFMA using social media analysis, bridging a gap in understanding beyond expert opinions. Through sentiment analysis and topic modelling of Reddit discussions, the study reveals predominantly positive attitudes towards POFMA, challenging prevailing narratives. Key findings from the sentiment analysis and topic modelling provide valuable insights into the public discourse surrounding POFMA and how it challenges preconceived notions about the perceptions of POFMA. The study contributes to the understanding of the complex interplay between legislative interventions, online discourse, and public opinion in the digital age.